(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was carried out to analyze the constraints experienced by the rural dairy farmers in Kamrup district of Assam. The study was conducted in 10 villages under 2 development blocks of Kamrup district by personally interviewing 200 dairy farmers. The respondents stated their constraint as high cost of feed, medicine and labour (72%); non availability of skilled labour (47%); lack of financial assistance (34%); small land holdings (22%); inadequate marketing channel (17%); high calf mortality (9%) and involvement of middlemen in marketing (7%).